Implementasi Scrum Agile Development Pada Sistem Informasi E-Mentor Di Kemahasiswaan IIB Darmajaya - Agarina, Melda; Sutedi, Sutedi (Politeknik Negeri Sriwijaya, 2021)
IIB Darmajaya Student Unit has a coaching program for students. . In the coaching program, students are given an understanding of how the world of Higher Education is true, as well as self-development through interactive and communicative learning simulations. The training program must be implemented for new students. In the activity there is a coaching class, new students will be accompanied by a mentor. This coaching program has a study weight equivalent to 2 credits that must be followed by new students. Mentors themselves are students selected by the Student Affairs Section based on personal abilities that have gone through several stages of the selection process, both the selection of file administration completeness, hardskill and softskill as well as micro teaching and interview stages. The role of mentors is to provide coaching, learning, and be responsible for work programs to early semester students for one semester. The duties and responsibilities of the mentors start from the new student administration process to the learning and assessment process of coaching program activities. Where the management of class administration and evaluation of activities are still carried out in a less efficient way and do not have an information system. This problem can be solved by using agile development system development methods with the Scrum model. Software or system development using the Scrum model has advantages in producing a system that suits the user's wishes. This website-based administrative and value processing information system can process classroom administration, search, update, store, recap student grades, and value reports that can be accessed easily and efficiently through the website.